Electrical properties of gamma-modified composites copolymer of polyvinylidene fluoride with tetrafluoroethylene and silicon - Nuruyev, I.M. (Вопросы атомной науки и техники, 2019)
The concentration and temperature dependences of the electrical properties of the composites obtained on the basis of a copolymer of polyvinylidene fluoride with tetrafluoroethylene P(VDF–TFE) with silicon nano- and microparticles were investigated, and the effect of gamma-radiation on them was studied. It is shown that the cause of the change in the concentration and temperature dependences of the electrical properties of irradiated composites P(VDF)–TeFE)/Si, apart from crosslinking and destruction, is the uneven distribution of the energy of the absorbed radiation between the components of the composite material. Досліджено концентраційні і температурні залежності електричних властивостей композитів, отриманих на основі сополімера полівініліденфториду з тетрафторетіленом P(VDF–TFE) з нано- і мікрочастинками кремнію, і вивчено вплив на них гамма-випромінювання. Показано, що причиною зміни в концентраційних і температурних залежностях електричних властивостей опромінених композитів P(VDF–TeFE)/Si крім зшивання і деструкції є і нерівномірний розподіл енергії поглиненого випромінювання між компонентами композитного матеріалу. Исследованы концентрационные и температурные зависимости электрических свойств композитов, полученных на основе сополимера поливинилиденфторида с тетрафторэтиленом P(VDF–TFE) с нано- и микрочастицами кремния, и изучено влияние на них гамма-излучения. Показано, что причиной изменения в концентрационных и температурных зависимостях электрических свойств облученных композитов P(VDF– TeFE)/Si кроме сшивания и деструкции является и неравномерное распределение энергии поглощенного излучения между компонентами композитного материала.